Elevation‐dependent changes in reference evapotranspiration due to climate change. Issue 26 (24th November 2020) - Sun, Juying; Wang, Genxu; Sun, Xiangyang; Lin, Shan; Hu, Zhaoyong; Huang, Kewei
Abstract: The Food and Agriculture Organizations' (FAO) Penman–Monteith reference evapotranspiration (ET0 ) is a crucial index in the research of water and energy balance. Temporal and spatial variations in ET0 from 1981–2017 were investigated in the Hengduan Mountains, China. The results showed a change point around the year 2000 in ET0 series. ET0 decreased and increased significantly by +3.200 mm/year ( p  < 0.01) from 1981–2000 and by +4.109 mm/year ( p  < 0.01) from 2001–2017, respectively. The contribution analysis shows that the positive significant contribution of air temperature (TA) was offset by negative effects of decreases in downward shortwave radiation (Rs ) and wind speed (WS) and an increase in actual vapour pressure (ea ), causing the decrease in ET0 from 1981 to 2000. WS was the largest contributing factor for the decrease in ET0 from 1981 to 2000 during spring, winter and annually, while Rs and ea were the largest negative contributors in summer and autumn, respectively. An increase in TA was responsible for the increase in ET0 in all seasons except winter and the annual scale in 2001–2017. The sensitivity analysis shows that ET0 was most sensitive to TA, and WS was the least sensitive variable. The trends of ET0 increased with elevation; we denote this as the elevation‐dependence of ET0 changes. The elevation‐dependence was also noted for the trends of WS and ea, with higher elevations showing larger changes in WS and lower changes in ea . Besides, the sensitivities of TA, Rs and ea decreased with elevation, while that of WS increased slightly with elevation. A comprehensive investigation into the trends of climatic drivers and their sensitivities revealed complex trends of the contributions of climatic variables on ET0 with elevation, with no uniform trend existed in seasons. The results will contribute to our understanding of the response of ET0 to climate change in a mountainous area, and provide a guideline for the water resources management under climate change. Abstract : The trends of ET0, WS and ea showed elevation‐dependency; The sensitivities of Rs, ea, and TA decreased with elevation, while that of WS increased with elevation; WS, ea and Rs together resulted in ET0 reduction in 1981–2000, and TA was responsible for the rise in ET0 in 2001–2017.